2009
DOI: 10.1007/s12284-009-9023-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Isolated Populations of Indonesian Landraces of Rice (Oryza sativa L.) Collected in East Kalimantan on the Island of Borneo

Abstract: Although the genetic diversity of rice germplasm has been well characterized globally, few studies have taken an in-depth view of a large number of rice landraces on a local scale. To better understand the relationships between rice genetic diversity and associated geographic and cultural factors, we collected and characterized 183 rice landraces from 18 villages along the Bahau and Kayan rivers in the Indonesian province of East Kalimantan on the island of Borneo. A genetic diversity analysis using 30 microsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 29 publications
4
19
3
Order By: Relevance
“…The allele number per locus is the highest among the rice collections that have been reported to date [37], [40], including an Indian germplasm collection [41], an Indonesian landrace collection [42] and a Brazilian rice core collection [43], with an exception of an Indonesian traditional and improved rice collection with 13 alleles per locus reported by Thomson et al [44]. The average polymorphic information content (PIC) value in this study was 0.71, which is also the highest among previous studies for rice populations [37], [40], [41], [42], [44], [45] with an exception of 0.75 PIC value in a study reported by Borba et al [43]. The wide range of genetic diversity along with the manageable number of accessions in the URMC makes it one of the best collections for mining valuable genes in rice.…”
Section: Discussionmentioning
confidence: 99%
“…The allele number per locus is the highest among the rice collections that have been reported to date [37], [40], including an Indian germplasm collection [41], an Indonesian landrace collection [42] and a Brazilian rice core collection [43], with an exception of an Indonesian traditional and improved rice collection with 13 alleles per locus reported by Thomson et al [44]. The average polymorphic information content (PIC) value in this study was 0.71, which is also the highest among previous studies for rice populations [37], [40], [41], [42], [44], [45] with an exception of 0.75 PIC value in a study reported by Borba et al [43]. The wide range of genetic diversity along with the manageable number of accessions in the URMC makes it one of the best collections for mining valuable genes in rice.…”
Section: Discussionmentioning
confidence: 99%
“…M olecular marker are a powerful tool for the characterization and evaluation of genetic diversity, population structure, and relationship in plant germplasm collections and have been applied to cultivated rice ( Oryza sativa L.) (Garris et al, 2005; Alvarez et al, 2007; Zeng et al, 2007; Thomson et al, 2007, 2009; Jayamani et al, 2007; Agrama et al, 2007; Agrama and Eizenga, 2008), weedy rice ( Oryza sativa L.) (Gealy et al, 2009; Cao et al, 2006), bread wheat ( Triticum aestivum L.) and wild emmer wheat [ Triticum turgidum L. subsp. dicoccoides (Körn.…”
mentioning
confidence: 99%
“…Rice is one of the most important food crops because it feeds more than half of the world's population (Khush, 1997). Molecular markers have been used to study genetic diversity and interrelationships for rice cultivars in the United States (Mackill, 1995; Xu et al, 2004; Garris et al, 2005; Caicedo et al, 2007), China (Zeng et al, 2007; Zhang et al, 2009), Indonesia (Thomson et al, 2007, 2009), Portugal (Jayamani et al, 2007), and Cuba (Alvarez et al, 2007). These studies focused on different areas: either a group of cultivars of specific interest, or germplasm accessions from a certain region, or a portion of a germplasm collection.…”
mentioning
confidence: 99%
“…This study directed to investigate and determine the genetic diversity and relationship of the tidal swamp rice germplasm of the South Kalimantan Province, Indonesia using the chloroplast trnL-F and nuclear IGS sequences. In a local scale, such studies could reveal the complex interaction between germplasm and farmers cultivation practices in good view [25]. Hence, the results of this study expected to be used as a reference in the rice genetic improvement and conservation program in the future.…”
Section: Introductionmentioning
confidence: 88%